Google Scholar versions: do more versions of an article mean greater impact?. Issue 4 (11th November 2014) - P. Pitol, Scott; L. De Groote, Sandra
Abstract : Purpose: – The growing dominance of Google Scholar (GS) as a first-stop resource for scholars and researchers demands investigation of its influence on citation patterns, freedom of information, and scholarly communication. The purpose of this paper is to break new ground in understanding the various versions GS indexes, correlations between the number of GS versions and citation counts, and the value of institutional repositories for increasing scholarly impact. Design/methodology/approach: – GS listings for 982 articles in several academic subjects from three universities were analyzed for GS version types, including any institutional repository versions, citation rates, and availability of free full-text. Findings: – First, open access articles were cited more than articles that were not available in free full-text. While journal publisher web sites were indexed most often, only a small number of those articles were available as free full-text. Second, there is no correlation between the number of versions of an article and the number of times an article has been cited. Third, viewing the "versions" of an article may be useful when publisher access is restricted, as over 70 percent of articles had at least one free full-text version available through an indexed GS version. Originality/value: – This paper investigates GS versions as an alternative source for a scholarly article. While other articles have looked at GS through various lenses, the authors believe this specific aspect of the topic has not been previously explored.